A Study in Differences Between Medium and High Levels of Factory Automation in Selected Semiconductor Device Manufacturers - Hamdan, Tahiruddin (2007)
Although the migration of new investments to regions with labour-cost advantage is more prevalent amongst labour-intensive manufacturing companies, it is a matter of time before competition intensifies even for technology-based manufacturers.